Cancer Care in the Community Setting: A Mixed Method Study - Rahayuwati, Laili; Ibrahim, Kusman; Nurhidayah, Ikeu; Komariah, Maria; Amelia, Vira; Cabanes, Ria C (STIKep PPNI Jawa Barat, 2025)
Aims: This study evaluated palliative care services in Indonesia, focusing on proposing a community-based model to enhance cancer care. Method: A mixed-method approach was employed, involving quantitative analysis of 200 patients’ personal and treatment factors and qualitative insights from 21 stakeholders to FGDs and in-depth interviews. Results: The qualitative results highlight five themes: 1) illness as a subjective and culturally influenced concept, 2) family’s role in treatment decision-making, 3) perceptions of healing through multiple treatment modalities, 4) finding positive meaning in illness, and 5) hopes and aspirations for recovery. The quantitative results show that 55.5% of patients had inadequate knowledge, with 69.5% preferring modern therapy. A significant relationship was found between knowledge, perception, and treatment options, while no significant correlation was observed with self-confidence or diagnosis date. Conclusion: An integrated community-based palliative care model tailored to Indonesia’s healthcare system is proposed to improve the quality of life for cancer patients.